2022
DOI: 10.3390/en15030907
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Local Authorities to Plan Energy Efficiency in Public Buildings: From Local Needs to Regional Planning

Abstract: The support offered to local authorities in this work consisted of technical and economic training on the integration of energy efficiency measures as well as the development of tools (guidelines, a decision support tool, databases and a visualization platform) that allow local authorities to prepare their building renovation plans. These tools are found very useful for local authorities, particularly in the case of Teruel province, characterised by many small municipalities whose local governments do not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Within this research, particular focus is placed on the processes and outcomes observed during the study conducted within the Portuguese regions. At the same time, some work has already been developed for other countries and regions (e.g., Teruel, Spain) [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this research, particular focus is placed on the processes and outcomes observed during the study conducted within the Portuguese regions. At the same time, some work has already been developed for other countries and regions (e.g., Teruel, Spain) [35].…”
Section: Methodsmentioning
confidence: 99%
“…The PrioritEE DSTool, which can be accessed online [32], enables local and regional authorities to evaluate the potential energy and financial savings achievable by implementing various measures to enhance the energy efficiency of individual public buildings and the entire building stock. The DSTool is currently being utilised by local administrations in the Mediterranean (MED) region, in Italy [34] and Spain [35], among others, to assess buildings' energy consumption and the cost-effectiveness of predefined measures, and to prioritise renovation actions and investments. The Decision Support Tool encompasses a comprehensive range of key performance indicators, and various intervention scenarios can be compared to analyse the impacts of the proposed strategies.…”
Section: Prioritee Dstool Descriptionmentioning
confidence: 99%
“…Herrando et al [20] presented a study describing the development of an energy action plan as a key and useful element offered to local authorities based on energyefficient measures and the integrated application of renewable resources in municipal public buildings. They also described the development of an energy plan referring to a decision support tool, database, and visualization platform, allowing local authorities to define suitable building renovation energy actions.…”
Section: Techno-economic Assessmentmentioning
confidence: 99%
“…Section 4 collects papers that address the topic of sustainable development for buildings, including energy supply and demand analysis (e.g., sediment heat energy [16], lifecycle analysis [17]) and lowtemperature direct heating and cooling (DHC) systems [18]. Section 5 collects papers that address the topic of techno-economic assessment of renewable systems (e.g., energy storage systems in microgrids [19] and smart control for hybrid renewable energy resources [20]) and environmental evaluation (especially for individual mountain huts [21] and building retrofit [22]). Eventually, Section 6 summarizes the main conclusions of the present review and the limitations of the current investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For such assessment, the energy efficiency label is potential solution widely praised for its simple and intuitive structure, easy-to-understand, small investment, and obvious benefits. Studies have shown that public buildings consume a great amount of energy during the entire life cycle, so their energy efficiency has received extensive attention from many researchers [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%